'Where' Else Could We Talk About?: The Border as Nomadic Site. (1st June 2014) - Ratliff, Jamie
Since 2005, Mexican artist Teresa Margolles has created a number of installations that address the drug- and gang-related violence that has plagued Mexico's northern border for the last two decades. Many of these artworks also share a decidedly spatial quality, as Margolles has physically transported material traces of criminal acts to secondary sites. Such site-oriented and performative techniques allow Margolles to present the border as 'nomadic', an unhinged site-specificity that widens the scope of the artist's inquiry from the direct experience of the actual space itself to investigate a larger discourse on the border. This article analyzes Margolles's What Else Could We Talk About? (2009), curated by Cuauhtémoc Medina, at the 53rd Venice Biennale. Through a theoretical framework of aesthetic and philosophical nomadism, I argue that the exhibition functioned as a critical intervention in producing the border as a space of social, political and institutional critique.